PENERAPAN LEARNING MANAGEMENT SYSTEM DAN BLENDED LEARNING SEBAGAI ALTERNATIF MODEL MERDEKA BELAJAR DI MASA ADAPTASI KEBIASAAN BARU PEMBELAJARAN AGAMA KRISTEN - Verawati, Herlina (Sekolah Tinggi Teologi Kristus Alfa Omega, 2020)
This paper describes the application of the Learning Management System and Blended Learning in the learning process of Christianity. The application of this learning system as an alternative to the Free Learning model during the adaptation period for New Normal in grade 4 Semester 1 students of SDN 8 Selat Hilir for the 2020/2021 academic year. The method used in this research is Classroom Action Research. The results showed that the application of the learning system used by Christian Religious Education teachers proved successful in improving student learning outcomes. This can be explained that in the pre-cycle the average score of student learning scores was 56.25 with 1 in 4 students completing. Furthermore, it increased in the first cycle, namely 68.75 with 2 students completing. Then in cycle II it increased again, namely 85.94 with 3 students who completed out of 4 students in class 4 Semester 1 in the 2020/2021 academic year at SDN 8 Selat Hilir. Likewise, the percentage of completeness increased from Pre-cycle 25%, increased in cycle I by 50%, and increased again to 70% in cycle II.